The impact of the removal of information and communication technology subjects on students' digital literacy - Siska Lestari; Popi Dayurni; Laksmi Evasufi Widi Fajari; Kyaw Zay Ya (Researcher and Lecturer Society, 2023)
This study aims to find out how the perception of class XI MA Darul Irfan students in Serang City about the abolition of ICT subjects, and also to determine the level of digital literacy skills of students in class XI MA Darul Irfan Serang City after the abolition of ICT subjects. The type of research used in this research is qualitative. Qualitative research is research that intends to understand the phenomena experienced by research subjects such as behaviour, perception, and motivation through descriptions in the form of words and language. So, in this study, researchers conducted observations, interviews and documentation. The results of the study show that: 1) ICT subjects are very important for students in schools to face the current digital era so that students are not ignorant about using technology. 2) the ability of students to find, manage, and convey information through digital is already high. Student's preparation to take advantage of digital literacy in learning is already high. The ability of students to think critically, creatively and innovatively in the use of technology is still low. Student participation in digital literacy activities is quite high.